Optimasi Perencanaan Produksi Pupuk NPK Menggunakan Metode Goal Programming - Bahij Naufal Qinthara Achmad; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
CV. Bumi Nusantara is a company engaged in the production of non-subsidized NPK fertilizer. The problem faced by the company is that production planning has been carried out based solely on estimates and experience without using a structured scientific method, resulting in the inability to accurately anticipate demand fluctuations. The Goal Programming method is used because it is capable of solving problems involving multiple objectives and priorities within a single mathematical model. The research data were obtained from production and demand data, machine capacity, labor, and production costs. The results of the study indicate that the Goal Programming method can produce a more optimal production plan by minimizing deviations from the targets set by the company. In addition, this method helps the company allocate resources effectively so that the production process becomes more directed. Therefore, the implementation of Goal Programming can serve as an alternative solution to improve the efficiency and effectiveness of NPK fertilizer production planning in the company.